Plausible predicament in emergency endodontic rehabilitation of a child with Sturge-Weber syndrome: A case report - Amit Khatri; Namita Kalra; Rishi Tyagi; Khadeeja Kulood M; Mayank Sharma; Drishti Kaushal (Arbu Academic Publishing, 2022)
Sturge-Weber Syndrome (SWS) is a neuro-oculo-cutaneous vascular disorder that includes leptomeningeal hemangioma and port wine stains, usually ipsilaterally, with ocular manifestations and extended lesions over the oral cavity. It is an embryonic developmental disorder affecting both mesodermal and ectodermal germ layers, associated with somatic mutation of gene GNAQ. It has a sporadic occurrence of 1:50,000 and no gender predilection. This case report added to the knowledge and understanding of systematic rehabilitation of a child patient with SWS and its associated risk factors in an emergency scenario. A 3.5-year-old girl child with a known diagnosis of SWS presented abscess over the right lower mandibular deciduous teeth and distinct oral features of SWS, requiring emergency endodontic intervention, followed by full mouth rehabilitation. Thus, an in-depth knowledge of the clinical state that helps in the expert assessment of dental interventions, including emotional co-regulation in those children, is essential.